The Protective Effects of Melatonin on Hainan Black Goats Under Heat Stress: Understanding Its Actions and Mechanisms - Hao Wu; Baochun Qin; Guang Yang; Pengyun Ji; Yu Gao; Lu Zhang; Bingyuan Wang; Guoshi Liu (Antioxidants)
As the global climate changes, high temperatures will cause heat stress, which significantly affects the productive efficiency of livestock. Currently, there is a lack of efficient methods to use in targeting this issue. In this study, we report that melatonin supplementation may represent an alternative method to reduce the negative impact of heat stress on livestock, particularly in Hainan black goats. Our results show that melatonin treatment increased the average daily gain of Hainan black goats that were exposed to constantly high temperatures for two months compared to controls. Our mechanistic exploration revealed that melatonin treatment not only reduced the oxidative stress and inflammatory reaction caused by heat stress but also improved goats’ metabolic capacity, promoting their growth and development. More importantly, for the first time, we observed that melatonin treatment modified the abundance of the intestinal microflora, altering the metabolism of the goats, which further improved their tolerance to constant heat stress.